Analisis Semiotik Iklan Layanan Masyarakat Anti Korupsi MTI dan ICAC - Handriyotopo Handriyotopo (Ornamen, 2006)
Campaign Anti Corruption has been declared as national movement. Those way campaigns which have been done by LSM Masyarakat Transparancy Indonesia represent positive effort to create good society and government and also to return the state authority in the world.Comment of advertisement of society service by MTI or ICAO (Independent Commission against Corruption) in many countries that have a high grade corruption quite enough to realize that the corruption will not bring the kindliness but will harm and break the nation and state. Societies require to be awaked from the importance of wipe out corruption up to its roots, because society doesnâ€™t aware the danger yet and corruption come to be culture. The Semiotic analyze of advertisement of society service by MTI and ICAC will get the meaning interpretation which is full of visual sign either through verbal and non verbal. Itâ€™s through the C.S. Pierce semiotics approach with Pierce triadic theory in semiosis course and Roland Bartesh in the mean expressed of sign by denotative and connotative.The making process of advertisement of society service needs creativity in expression of advertisement communication procedure. There is 11 masterpiece of anti corruption advertisement of society service which is analyzed with semiotic approach that writer take away from the MTI website. The advertisements have been published around 1998 to 2001.Keyword: semiotic, anti corruption, semiosis, denotative, connotative, myth, sign of adverstisement of society serviceÂ